PENGARUH RISIKO AUDIT, TINDAKAN SUPERVISI DAN PROSEDUR REVIEW TERHADAP PENGHENTIAN PREMATUR ATAS PROSEDUR AUDIT - Ni Wayan Vega Juniyanti; Ni Komang Sumadi (UNHI Press, 2021)
This. study the effect of audit. risk, supervision measures, and review procedures on premature.Termination. Of. Audit. procedures. Population in this study were all auditors who worked at the State Audit Board of the Republic of Indonesia, representing the Province of Bali, totaling 60 auditors, and the entire population in this study was sampled, namely 60 auditors. Datacollection techniques in this study using a questionnaire (questionnaire). The method of determining the sample using purposive sampling method. The data analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that audit risk has no effect on premature termination of audit procedures. Partially, only review procedures have a negative and significant effect. on premature .termination. of .audit procedures at BPK RI Representatives of Bali Province, while audit risks and supervision measures have no effect on premature termination of audit procedures at BPK RI Representatives of Bali Province.